PROBLEMS AND SOLUTIONS IN STUDYING THE MODERN DESIGN OF MUSEUM INTERIORS - D. Sh. Saipova; Sh. ?. Mirziyoev (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The project of museums in Uzbekistan combines the ideas of modernity and nationalism, promotes the creative work of people of all ages, including young people, develops their abilities, raises their spiritual and cultural level, and promotes creative design in all its aspects.